Analisis Pencapaian Akreditasi Paripurna Di PUSKESMAS Teupah Tengah Kabupaten Simeulue - Wahyu Swandarini; Tri Niswati Utami; Nur’aini Nur’aini (Journal of Health and Medical Science, 2023)
Community health center is a place for public health services to improve the quality of service, it is necessary to accredit the puskesmas. Many things are needed to achieve maximum accreditation. One of them is plenary accreditation. The problem in this research is the difficulty for puskesmas to achieve plenary accreditation. The purpose of this research is to analyze the achievement of plenary accreditation. This type of research uses qualitative methods with a descriptive study design. The informants of this research were conducted with 5 informants including the head of accreditation quality, the head of the health center, a member of the board, the accreditation companion team from the Health Office and the head of the Working Group Admen. Data collection techniques are using interviews and observation. Data analysis used in this research is reduction, display and triangulation. The results showed that the provision of funds had never existed and was given to the community health center, human resources were still lacking such as pharmacy staff, administration staff, environmental health and laboratories and there were still several problems such as limited land, lack of computers, printers and several other tools so that it became an obstacle in work. The conclusion in this study is that there are still delays in the disbursed budget for the accreditation of the community health center, there are still inadequate human resources, incomplete facilities and infrastructure, communication is carried out well and the bureaucratic structure and disposition have not been carried out properly. It is hoped that the Head of the Health Service is obliged to support, motivate, evaluate, monitor and expedite the process of achieving the plenary accreditation of the community health center.